2022
DOI: 10.1155/2022/1946724
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Role of Nanoparticles in Environmental Remediation: An Insight into Heavy Metal Pollution from Dentistry

Abstract: Environmental damage is without a doubt one of the most serious issues confronting society today. As dental professionals, we must recognize that some of the procedures and techniques we have been using may pose environmental risks. The usage and discharge of heavy metals from dental set-ups pollute the environment and pose a serious threat to the ecosystem. Due to the exclusive properties of nanosized particles, nanotechnology is a booming field that is being extensively studied for the remediation of polluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 122 publications
(117 reference statements)
0
13
0
Order By: Relevance
“…However, scientists present the solution for remediation of heavy metal poisoning in waste dental water using NPs only. These specified nano pollution absorbers and efficiently eradicate heavy metals from water due to their higher surface area and porous nature [ 154 ].y…”
Section: Application Of the Nano Dentistrymentioning
confidence: 99%
“…However, scientists present the solution for remediation of heavy metal poisoning in waste dental water using NPs only. These specified nano pollution absorbers and efficiently eradicate heavy metals from water due to their higher surface area and porous nature [ 154 ].y…”
Section: Application Of the Nano Dentistrymentioning
confidence: 99%
“…This provides silver nanoparticles with an important anticariogenic effect at low toxicity [33][34][35]. Furthermore, previous studies have found that the incorporation of silver nanoparticles did not affect the cytotoxicity of human cells.…”
Section: Discussionmentioning
confidence: 95%
“…It is reported that fabricating scaffolds with optimal pore size, it is possible to maintain oxygen tension and pH levels inside a scaffold that are nearly identical to values measured on the scaffold's exterior. These scaffolds, known as oxygen tension controlled matrices, have been shown in vitro and in static culture to support cell proliferation and mineralization throughout the scaffold structure (i.e., fully osteoconductive), and they may have the potential to repair largescale or critical-size bone defects in vivo (35)…”
Section: Scaffold Porositymentioning
confidence: 99%